A Mutation in Damage-Specific DNA Binding Protein One (ddb-1) Underlies the Phenotype of the No-Marginal-Zone (nmz) Mutant Zebrafish - Kailey Jerome; Aria Gish; Taylor Aakre; Taylor Brend; Mara Kate Grenier; Christina L. Johnson; Jaxon Gronneberg; Colin K. O’Neill; Lucas Radermacher; Tristan Darland (Fishes, 2025)
The ciliary marginal zone (CMZ) is a region in the peripheral-most retina that displays ongoing retinogenesis during growth and expansion of the eye in adulthood. While there is evidence that this capacity also exists in birds and mammals, it is far more robust in fish and amphibians. The process of CMZ retinogenesis is essentially equivalent to that seen early in the central retina; however, its regulation is not fully understood. In a previous study, we attempted to uncover novel regulatory genes by using a forward genetics screen in zebrafish, looking for recessive CMZ mutants. One of the mutants found was called no marginal zone (nmz). The nmz mutant showed relatively normal central retina development, but a lack of cells in the CMZ by 5 days post fertilization (dpf). Mapping, genomic sequencing, and complementation analysis using a second mutant line (m863) isolated in another laboratory showed that a mutation in damage-specific DNA binding protein-1 (ddb-1) gene underlies the phenotype seen in nmz. BrdU labeling suggested that later expansion and differentiation of CMZ retinal progenitors is more affected by ddb-1 loss than the earlier process of stem cell asymmetric division. As was seen for the m863 mutant and in other studies with mice, one profound effect of ddb-1 loss in nmz was the upregulation in expression of tp53 and several of its downstream effectors. Several important genes important in CMZ retinogenesis are also downregulated in the nmz mutant. The change in gene expression would suggest that ddb-1 loss leads to increased cell cycle disruption and apoptosis at the expense of CMZ retinogenesis. While homozygosity is lethal, heterozygous fish appear to be completely normal in morphology, visual function, and behavior.

Notes on the experimental laboratory and field culture of Lessonia variegata (Laminariales) - Kate Neill; Sheryl Miller; Wendy Nelson (New Zealand Journal of Marine and Freshwater Research, 2025)
The kelp Lessonia variegata J. Agardh (Lessoniaceae) is a potential aquaculture target for bioactive compounds. We investigated the control and management of Lessonia gametogenesis, the settlement and retention of sporophytes on various culture strings, and the upscaling of string settlement for field trials. In the laboratory we held gametophytes at low light conditions for 2.5 months before altering conditions to stimulate them into the next part of the life cycle. Settlement and development of sporophytes was highest on Korean culture string, followed by Builders Line, however after agitation, fewer sporophytes were dislodged from the Builders Line. Larger scale settlement of spores onto 15 m lengths of Builders Line was successful, with sporophytes reaching ∼5 mm length in 46 days. Eight weeks after out‐planting, the sporophytes were heavily fouled with other algae. Although the results presented here were small‐scale and lack replication, they add to the existing knowledge on the biology and cultivation of this species.

Modelling the influence of road elevation on pollutant dispersion - James O’Neill; Martin Seaton; Kate Johnson; Jenny Stocker; Rohan Patel; Martine Van Poppel; David Carruthers (Air Quality, Atmosphere & Health, 2024)

The impact of graphic design on attention capture and behavior among outdoor recreationists: Results from an exploratory persuasive signage experiment - William L. Rice; Jeremy Shellhorn; Victoria Bloomgren; Lily Booth; Sarah Duncan; Jazzelle Elias; Keaton Flowers; Isabella Gambini; Abigail Gans; Adri Medina; David Obadare; Connor O'Neill; et al. (Journal of Outdoor Recreation and Tourism, 2023)

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Cryptofauna associated with rhodoliths: Diversity is species‐specific and influenced by habitat - María del Carmen Méndez Trejo; Kate F. Neill; Brenton A. Twist; Wendy A. Nelson (Marine Ecology, 2021)
Rhodoliths are recognised as providing critical ecosystem services in nearshore systems through habitat provision. We tested the influence of rhodolith hosts and habitat on the diversity and composition of sessile and motile invertebrates found associated with two species of rhodolith. Investigations of cryptofauna were undertaken at three beds within the Bay of Islands, northern New Zealand. Lithothamnion crispatum , which was smaller in overall size, and had less free space and a smaller internal volume than Sporolithon sp., provided habitat for more species of distinct life forms, both motile and sessile species, than Sporolithon sp. Although there were few differences in the dimensions of L . crispatum found in the beds, there was significantly more free space available in Sporolithon sp. rhodoliths found in one of two beds where it occurred, and the associated cryptofaunal richness of both sessile and motile species was significantly higher in this population. This study revealed species‐specific differences in the rhodolith‐associated cryptofauna and a significant impact of rhodolith habitat on growth form and cryptofaunal assemblages at the sites investigated in one of the host species ( Sporolithon sp.). Understanding interactions between species and habitats provided by rhodoliths is critical to understanding the nature of ecosystem services provided in these biogenic habitats.

The Genetic Education for Men (GEM) Trial: Development of Web-Based Education for Untested Men in BRCA1/2-Positive Families - Beth N. Peshkin; Mary Kate Ladd; Claudine Isaacs; Hannah Segal; Aryana Jacobs; Kathryn L. Taylor; Kristi D. Graves; Suzanne C. O’Neill; Marc D. Schwartz (Journal of Cancer Education, 2021)

Male guppies differ in daily frequency but not diel pattern of display under daily light changes - Samuel J. O’Neill; Thomas E. White; Kate E. Lynch; Darrell J. Kemp (Behavioral Ecology and Sociobiology, 2019)

Growth and carrageenan composition of two populations of the New Zealand carrageenophyte Sarcothalia lanceata (Gigartinaceae, Rhodophyta) - Kate Neill; Wendy Nelson; Catriona Hurd; Ruth Falshaw (Journal of Applied Phycology, 2018)

Seeing complexity: visualization tools in global environmental politics and governance - Kate O’Neill; Erika Weinthal; Patrick Hunnicutt (Journal of Environmental Studies and Sciences, 2017)

Beyond diving depths: deepwater macroalgae in the New Zealand region - Wendy Nelson; Kate Neill; Roberta D’Archino; Tara Anderson; Jenny Beaumont; Jenn Dalen (Marine Biodiversity, 2015)

Territories of Chance Meet Territories of Choice - Kate O'Neill (Conservation Biology, 2007)

DMXB, an ?7 nicotinic agonist, normalizes auditory gating in isolation-reared rats - Heidi C. O'Neill; Kate Rieger; William R. Kem; Karen E. Stevens (Psychopharmacology, 2003)